Pengaruh Akupresur dengan Murottal Ar-Rahman Terhadap Penurunan Nyeri Dismenore pada Siswi SMP Negeri 2 Giriwoyo - Haniifah Nur Hasanah; Winarni Winarni (Pusat Riset dan Inovasi Nasional, 2025)
Background: Dysmenorrhea, characterized by pain around the abdomen, waist, and lower back, arises due to increased prostaglandin hormone levels during menstruation. If left untreated, this pain will disrupt the daily activities and academic performance of adolescent girls. Management can be achieved through the use of acupressure and listening to the recitation of the Qur'an, both of which are safe and effective in alleviating pain, promoting relaxation, and obtaining the blessings of Allah SWT. The objectives of the research: This study aims to evaluate the impact of acupressure therapy with Ar-Rahman murottal on the reduction of dysmenorrheic pain in students of SMP Negeri 2 Giriwoyo Methods: This research employs a quasi-experimental design with a pretest-posttest non-equivalent control group approach. The study sample consists of 36 respondents selected through a purposive sampling technique. Data analysis was performed using the Mann-Whitney test to compare the treatment and control groups. Results: he dysmenorrhea pain scale in the treatment group significantly decreased compared to the control group, with a P-value of 0.016 < α 0.05. Acupressure therapy combined with the recitation of Surah Ar-Rahman was effective in reducing dysmenorrhea pain in female students at SMP Negeri 2 Giriwoyo. Summary: This study concludes that acupressure therapy combined with the recitation of Surah Ar-Rahman can be an effective alternative for alleviating dysmenorrhea pain in adolescent girls.